2020
DOI: 10.9734/aprj/2020/v5i130096
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Alkali Extracted Starches from Selected Cereals and Tubers

Abstract: Aims: Starch is used in the food industry to impart functional properties and to modify food texture and consistency. In this study starches isolated from six sources using an alkali extraction method were evaluated for physicochemical properties. Study Design: Complete randomized design. Place and Duration of Study: Department of Food Science and Technology, Faculty of Livestock, Fisheries, & Nutrition, Wayamba University of Sri Lanka, Makandura, Gonawila (NWP), Sri Lanka between April 2017 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Starch from traditional black rice and sorghum was extracted using the alkali method (Wijesinghe & Gunathilake, 2020). The procedures used for the extraction of starch are as shown in Figure 1.The starch yield was calculated using the following equation.…”
Section: Starch Extractionmentioning
confidence: 99%
See 3 more Smart Citations
“…Starch from traditional black rice and sorghum was extracted using the alkali method (Wijesinghe & Gunathilake, 2020). The procedures used for the extraction of starch are as shown in Figure 1.The starch yield was calculated using the following equation.…”
Section: Starch Extractionmentioning
confidence: 99%
“…From Figure 2, it can be observed that the starch yield of traditional black rice and sorghum was found to be 50.14% and 44.78% respectively. Less yield of starch is due to lower dispersibility and solubility of glutens present in the sample, and also difficulties in filtering due to an increase in viscosity of sample slurry (Wijesinghe & Gunathilake, 2020).…”
Section: Starch Yieldmentioning
confidence: 99%
See 2 more Smart Citations